417. ROBOT-ASSISTED MINIMALLY INVASIVE ESOPHAGECTOMY WITH UPPER MEDIASTINAL LYMPHADENECTOMY. (24th September 2022) - Tsunoda, Shigeru; Nishigori, Tatsuto; Hisamori, Shigeo; Maekawa, Hisatsugu; Hoshino, Nobuaki; Hanada, Keita; Yoshida, Shinya; Nishiyama, Kazuhiro; Obama, Kazutaka
Abstract: We started robot-assisted minimally invasive esophagectomy (RAMIE) in 2012 using da Vinci S. After the reimbursement in the national insurance system in 2018, RAMIE has been indicated as an institutional standard surgery simply depending on the da Vinci availability. Our early series of 45 RAMIEs showed significantly less postoperative morbidity (p = 0.03) mainly due to less pulmonary complication (p = 0.006) compared to conventional minimally invasive esophagectomy using propensity score matching (Ann Surg Oncol. 2020). This study aims to retrospectively evaluate the feasibility of RAMIE and to demonstrate our standardized RAMIE with updated data. Our surgical technique is as follows. A patient is placed in a prone position with both lung ventilation with 8-10 mmHg artificial pneumothorax. In the upper mediastinum, the thoracic duct is usually preserved unless there is tumor invasion. Then, the tracheoesophageal arteries flowing into the visceral sheath over the recurrent laryngeal nerve (RLN) are divided first and RLN is isolated laterally. Then, the lymphatic tissue is dissected from the trachea. This procedure is identical on both sides of RLN nodal dissection. By January 2022, 89 RAMIEs (S: 6 cases and Xi: 83 cases) were performed. Thoracic operation time was 348 min and console time was 296 min. Intraoperative blood loss was 80 g and the number of harvested thoracic nodes is 23. There was no conversion from RAMIE to MIE nor to open procedure. Overall severe postoperative morbidity (Clavien-Dindo Grade 3 or higher) was 17% (15/89) and clinically relevant postoperative recurrent laryngeal nerve palsy (Clavien-Dindo Grade 2 or higher) was 10% (9/89). There was no postoperative mortality. RAMIE was safe and feasible.